Approximation Properties of Generalized λ-Bernstein–Stancu-Type Operators - Qing-Bo Cai; Gülten Torun; Ülkü Dinlemez Kantar (Journal of Mathematics)
The present study introduces generalized λ-Bernstein–Stancu-type operators with shifted knots. A Korovkin-type approximation theorem is given, and the rate of convergence of these types of operators is obtained for Lipschitz-type functions. Then, a Voronovskaja-type theorem was given for the asymptotic behavior for these operators. Finally, numerical examples and their graphs were given to demonstrate the convergence of Gm,λα,βf,x to fx with respect to m values.